Managing cultivated pastures for improving soil quality in South Africa: challenges and opportunities - Swanepoel, Pieter A; Botha, Philip R; du Preez, Chris C; Snyman, Hennie A; Labuschagne, Johan (African journal of range & forage science, 2015)
Loss of productive agricultural land due to soil degradation poses a serious threat to agricultural output and sustainability. Soil degradation of cultivated pastures manifests as a long-term decline in production potential. There are concerns that soils under pastures in certain regions of South Africa are degrading as a result of mismanagement, which include practising continuous tillage, improper grazing management, injudicious application of fertilisers and poor irrigation management. Soil quality indicators, which include physical, chemical and biological parameters in soil, are science-based methods to monitor sustainability and protect soil. Soil quality data informs the land manager in the decision-making process to address practices that degrade agro-ecological systems and mitigate any loss of function. The aim of this paper is to provide a synthesis of the challenges and opportunities in soil management of pastures. The value of assessing soil chemical, physical and biological indicators to monitor soil quality is stressed.